PENGEMBANGAN PRODUK “PUKHI” PUDING UBI UNGU DAN KACANG HIJAU SEBAGAI SNACK PASIEN DIABETES MELLITUS TIPE 2 - Nirma Maretasari; Fitria, Mona; Isdiany, Nitta; Suparman, Suparman (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
The 2023 Indonesian Health Survey (SKI) showed that the prevalence of diabetes mellitus (DM) diagnosed by doctors in Indonesia was 2.2%. Dietary regulation, particularly the intake of nutritious snacks that are high in fibre, low in sugar, and possess a low glycaemic index, is crucial for the prevention and management of type 2 diabetes mellitus. Purple sweet potatoes and mung beans are local foods rich in complex carbohydrates, low glycaemic index, vegetable protein, fibre, and antioxidants. This study aims to evaluate the impact of purple sweet potato and mung bean formulations on the quality of the snack